Beclin-1- mediated autophagy may be involved in the elderly cognitive and affective disorders in streptozotocin-induced diabetic mice. Issue 1 (December 2016) - Guan, Zhu-Fei; Zhou, Xiu-Ling; Zhang, Xiao-Ming; Zhang, Yu; Wang, Yan-Mei; Guo, Qi-Lin; Ji, Gang; Wu, Guo-Feng; Wang, Na-Na; Yang, Hao; Yu, Zhong-Yu; Zhou, Hou-Guang; et al.
Abstract Background Diabetes is the most common metabolic disease with many chronic complications, and cognitive disorders are one of the common complications in patients with diabetes. Previous studies have showed that autophagy played important roles in the progression of metabolic syndrome, diabetes and other diseases. So we investigated whether aged diabetic mice are prone to be associated with the cognitive and affective disorders and whether Beclin-1-mediated autophagy might be involved in thepahological process. Methods High-fat diet/streptozotocin (STZ) injection-induced diabetic C57 mice were adopted in this study. Cognitive disorders were detected by Morris water maze and fear conditional test. Affective disorders were detected by tail suspension test and forced swimming test. Magnetic resonance imaging was applied to observe changes of morphology and metabolism in the brain. The 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) was used to assess metabolism changes in the brain of aged diabetic mice. Autophagy were evaluated by Beclin- 1, LC3II/I and P62, which were detected by western blot analysis and observed by electron microscopy. Results 1. Compared with control group, diabetes mice showed significantly decreasing abilities in spatial memory and conditioned fear memory (allP  < 0.05), and increasing tendency of depression (P  < 0.05). 2. MRI showed that the majority of elderly diabetic mice were associated with multiple cerebral small vessel disease. Some even showed hippocampal atrophy, ventricular dilatation and leukoaraiosis. 3. FDG-PET-CT discovered that the glucose metabolism in the amygdala and hippocampus was significantly decreased compared with normal aged mice (P  < 0.05). 4. Electron microscopy found that, although autophagy bodies was not widespread, and there was no significant difference between the two groups, yet compared with normal aged mice, apparent cell edema, myelinated tow reduction and intracellular lipofuscin augmentation existed in elderly diabetic mice brain. 5. The level of p62 was increased in the STZ-induced diabetic mice hippocampus and striatum, and beclin1 protein expression were significantly decreased in diabetic mice hippocampus compared with normal aged mice (P  < 0.05). There was a upward trend of the ratio of LC3II/I in hippocampus, cortex and striatum, but no statistically difference between the two groups. Conclusion Compared with normal aged mice, diabetic aged mice were apt to cerebral small vessel disease and associated with cognitive and affective disorders, which may be related to the significantly reduced glucose metabolism in hippocampus and amygdala. Beclin1 mediated autophagy in hippocampus probably played an important role in cognitive and affective disorders of STZ-induced aged diabetic mice.